Budget impact model of avelumab in patients with metastatic merkel cell carcinoma in the US - Bharmal M; Kearney M; Zheng Y; Phatak H (ClinicoEconomics and Outcomes Research, 2019)
Murtuza Bharmal,1 Mairead Kearney,1 Ying Zheng,2 Hemant Phatak21Global Evidence and Value Development, Merck Healthcare KGaA, Darmstadt, Germany; 2US Health Economics and Outcomes Research, EMD Serono, Inc, Rockland, MA, USAObjective: To estimate the budget impact of avelumab as a treatment option for patients with treatment-naïve first-line (1L) and previously treated second-line or later (2L+) metastatic Merkel cell carcinoma (mMCC) in the US.Methods: A budget impact model was developed to evaluate the addition of avelumab for the treatment of mMCC patients using a hypothetical 30 million-member US health plan over a 3-year time horizon (2019–2021). The comparator treatments included in the analysis were pembrolizumab and nivolumab (other immuno-oncology agents); and the chemotherapies routinely used in the eligible mMCC population. Model inputs included market share uptake of avelumab and other comparators, duration of treatments, and costs (drugs, health care resource utilization, adverse events). The model was evaluated from a commercial payer perspective. Sensitivity analyses were conducted to test uncertainties arising from the input values used in the model.Results: In a hypothetical commercial health plan of 30 million members, 285 patients with mMCC were identified over 3 years; 43 patients received avelumab as a 1L treatment over 3 years. In a world without avelumab, the total health care costs of treating patients with mMCC over 3 years were estimated to be US$11,710,115 from a commercial health plan perspective. With avelumab, there were estimated savings of $2,643,173 considering the total costs related to the treatment of mMCC over 3 years (23% reduction in the budget). The incremental cost per member per month over 3 years was −$0.0025.Conclusion: The model results indicate that the adoption of avelumab as a treatment option for mMCC would likely result in minimal budget impact from a US health plan perspective. Patients with mMCC, a rare condition with a poor prognosis and high unmet need, may benefit greatly from recently approved immunotherapies.Keywords: metastatic merkel cell carcinoma, cost, budget impact model, avelumab